Teachers' and Students' Views on AI Writing Tools' Adverse Effects in EFL Writings - Zahra, Mutia; Rahmah Fithriani (Universitas Cokroaminoto Palopo, 2025)
This study investigated the adverse effects of AI writing tools in English as a Foreign Language (EFL) contexts and explored strategies employed by teachers and students to address these challenges. The research utilized a qualitative case study approach, involving 10 EFL students and 2 teachers from a private senior high school in Medan, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis over one week. Data analysis employed Braun and Clarke's six-phase thematic analysis framework, which involved thorough reading of transcripts, initial coding of relevant statements, theme identification, review and refinement of themes, defining and labeling, and final report generation. The findings revealed three significant concerns: a decline in learning autonomy and critical thinking, deterioration of genuine writing progression, and challenges in evaluation and academic integrity. Students exhibited increased dependency on AI tools, leading to standardized writing styles and diminished ability to engage in independent problem-solving. To address these issues, three primary strategies emerged: developing explicit ethical guidelines for AI tool usage, implementing activities that promote creativity and innovative thinking, and repositioning AI as an educational tool rather than a substitute for human effort. The study demonstrates that while AI writing tools offer immediate assistance, they often create a counterproductive cycle of dependency that compromises essential language learning objectives. The findings underscore the importance of maintaining a balance between technological advancement and authentic language acquisition, suggesting that AI tools, while valuable educational resources, require careful regulation to preserve the fundamental human aspects of language learning and academic development. This research contributes to the existing literature by providing comprehensive insights into the challenges and adaptation strategies within EFL environments.